2005
DOI: 10.1093/jn/135.12.2866
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Indicator Amino Acid Oxidation Technique to Determine the Availability of Amino Acids from Dietary Protein in Pigs

Abstract: Standardized ileal ("true") digestibility is currently the best estimate of amino acid digestibility, but it does not measure bioavailability. Growth assays to determine amino acid bioavailability are expensive and laborious; thus, a rapid method is needed. Applying the principle of slope-ratio assay to the indicator amino acid oxidation (IAAO) method, we hypothesized that the reduction in indicator oxidation per gram of lysine in feedstuffs relative to that per gram of free lysine represented the bioavailabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 16 publications
3
76
1
Order By: Relevance
“…Thus, observations of improved weight gain response of pigs to increased dietary thr in the present study could be interpreted as arising from increased protein synthesis and deposition. Recently, Moehn et al (2005) showed that the indicator amino acid oxidation method can be used in pigs to determine the metabolic availability of lysine in dietary proteins for protein synthesis. This new method is based on the principle of standard curve growth assays and the inverse effect of the limiting amino acid on protein synthesis relative to the utilization of other amino acids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, observations of improved weight gain response of pigs to increased dietary thr in the present study could be interpreted as arising from increased protein synthesis and deposition. Recently, Moehn et al (2005) showed that the indicator amino acid oxidation method can be used in pigs to determine the metabolic availability of lysine in dietary proteins for protein synthesis. This new method is based on the principle of standard curve growth assays and the inverse effect of the limiting amino acid on protein synthesis relative to the utilization of other amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly used variables in a slope-ratio assay are weight gains and gain : feed ratio (Adeola, 1996). Recently, Moehn et al (2005) reported the development of a supposedly more rapid and less-expensive method for determining metabolic amino acid availability in foods. Information is accruing on amino acid bioavailability for younger pigs (Kovar et al, 1993;Adeola et al, 1994;Moehn et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The most recent protein requirement report (WHO, 2007) noted the potential promise of using 24-hour IAAO balance instead of or in addition to 24-hour nitrogen balance for the determination of amino acid requirements of humans. A method, based upon the IAAO technique, was developed to measure the metabolic availability of the limiting amino acid in the diet of pigs (Levesque et al, 2010;Moehn et al, 2005Moehn et al, , 2007 and subsequently adapted to humans (Humayun et al, 2007, Prolla et al, 2013. In the pig, the values obtained by IAAO are not different from those obtained by 'true' ileal digestibility.…”
Section: The Indicator Amino Acid Oxidation (Iaao) Methods Backgroundmentioning
confidence: 99%
“…Phenylalanine, in the presence of excess tyrosine, fi ts all four criteria. L-1-13 C-Phenylalanine has been successfully used to measure metabolic availability in pigs (Levesque et al, 2011;Moehn et al, 2005Moehn et al, , 2007 and humans (Humayun et al, 2007;Prolla et al, 2013). It is possible that other amino acids, such as leucine, are usable as tracers; however, to date phenylalanine has been used in these protocols to determine dietary bioavailability of amino acids.…”
Section: Choice Of Indicator Amino Acidmentioning
confidence: 99%
“…The slope-ratio assay for protein deposition is considered the best approach to assess the bioavailability of AA (Batterham, 1992). The indicator AA oxidation technique (IAAO; Moehn et al, 2005) can be used in slope-ratio assays and can be accomplished much more rapidly than a conventional slope-ratio assay which uses the outcome parameters of both protein and fat deposition, as measured in growth studies. The IAAO technique reflects the change in protein synthesis of animals with increasing AA intake; as protein synthesis increases, the oxidation of the indicator AA (phenylalanine (Phe)) decreases proportionately (Ball and Bayley, 1986;Zello et al, 1995;Elango et al, 2008).…”
Section: Introductionmentioning
confidence: 99%